Effects of Scaffolding on English Language Learners’ Academic Buoyancy - Ayiera, Eunice Kerubo; Owaa, Judith; Mwebi, Benard (American Journal of Education and Practice, 2025)
Purpose: The study investigated the effects of scaffolding on English language learners’ academic buoyancy as informed by social cultural theory, supported by cognitive load theory. Materials and Methods: Sequential explanatory design within the mixed methods approach was adopted involving 364 learners of English language and 10 teachers who were picked out through purposive sampling from four secondary schools in Kenyenya Sub-County, Kenya. Quantitative data was collected using Solomon-four non-equivalent quasi experimental group design while qualitative data was collected using interview technique. Instruments of data collection were pre-test and post-test questionnaires adapted from Martin and Marsh (2008), scaffolding modules and interview schedules. Internal validity of the questionnaires was investigated using Kaiser-Meyer-Oklin (KMO Index) and Bartlett’s Test of Sphericity, while validity of the experiment was ensured using 2 intervention and 2 control groups. Reliability of the pre-test and post-test questionnaires was established using split half and Cronbach’s Alpha techniques. Quantitative data was analyzed by frequency percentages, mean, standard deviation and t-test analysis using the SPSS package version 26.0 while qualitative data was analyzed thematically. Findings: Pre-post questionnaire results revealed that the posttest mean scores of academic buoyancy among the experimental groups were significantly higher than those of the control groups. The paired samples t-test showed a statistically significant effect of scaffolding learning on academic buoyancy. From qualitative data, the study established that scaffolding led to an improvement in academic buoyancy among the learners of English language. Therefore, scaffolding learning process enhanced academic buoyancy of learners. Implications to Theory, Policy and Practice: The Ministry of Education should retrain teachers on scaffolding teaching to empower and refresh teachers’ knowledge, since scaffolding learning is very effective in enhancing learners’ academic buoyancy.